Political Participation in Nursing Homes: Ethnography of an Elusive Object - Meigniez, Maëlle; Lucas, Barbara; Sgier, Lea (Swiss Journal of Sociocultural Anthropology, 2021)
This article aims to illustrate the usefulness of an ethnographic approach for the understanding of how institutionalised older people relate to voting and political participation. Based on fieldwork in six nursing homes in French speaking Switzerland, we show how behind an apparent lack of interest in politics and a disengagement from voting, there is sometimes a strong interest that just needs to be heard. This leads us to a twofold conclusion: that the “civic death” that often comes with institutionalisation is not an age-related fatality, but (partly at least) the effect of an (evitable) institutional “avoidance” of politics by the institutional context itself; and that an ethnographic approach is key to uncover the relationship of older people to politics, often buried under social norms or feelings of incompetence, or made invisible in everyday life